2021
DOI: 10.1155/2021/6649085
|View full text |Cite|
|
Sign up to set email alerts
|

Microbiome-Metabolomics Reveals Endogenous Alterations of Energy Metabolism by the Dushen Tang to Attenuate D-Galactose-Induced Memory Impairment in Rats

Abstract: Aging affects the brain function in elderly individuals, and Dushen Tang (DST) is widely used for the treatment of senile diseases. In this study, the protective effect of DST against memory impairment was evaluated through the Morris water maze (MWM) test and transmission electron microscopy (TEM). A joint analysis was also performed using LC-MS metabolomics and the microbiome. The MWM test showed that DST could significantly improve the spatial memory and learning abilities of rats with memory impairment, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 67 publications
(69 reference statements)
0
12
0
Order By: Relevance
“…As for the countries where the experiments were conducted, China had the most cases (n = 20) [ 8 , 9 , 13 , 15 , 16 , 19 , 23 , 26 , 27 , 28 , 29 , 30 , 32 , 36 , 38 , 39 , 46 , 47 , 48 , 49 ], followed by Japan (n = 8) [ 12 , 20 , 40 , 41 , 42 , 43 , 44 , 45 ], Korea (n = 6) [ 24 , 31 , 33 , 34 , 35 , 37 ] and Taiwan (n = 3) [ 21 , 22 , 23 ]. Thailand [ 18 ], the United States [ 17 ], Mexico [ 11 ] and Poland [ 25 ] were each associated with one study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As for the countries where the experiments were conducted, China had the most cases (n = 20) [ 8 , 9 , 13 , 15 , 16 , 19 , 23 , 26 , 27 , 28 , 29 , 30 , 32 , 36 , 38 , 39 , 46 , 47 , 48 , 49 ], followed by Japan (n = 8) [ 12 , 20 , 40 , 41 , 42 , 43 , 44 , 45 ], Korea (n = 6) [ 24 , 31 , 33 , 34 , 35 , 37 ] and Taiwan (n = 3) [ 21 , 22 , 23 ]. Thailand [ 18 ], the United States [ 17 ], Mexico [ 11 ] and Poland [ 25 ] were each associated with one study.…”
Section: Resultsmentioning
confidence: 99%
“…In herbal medicine extraction, 17 studies used water extraction [ 9 , 13 , 14 , 17 , 20 , 21 , 22 , 27 , 31 , 33 , 39 , 40 , 42 , 45 , 47 , 48 ]; 6 studies used ethanol [ 10 , 16 , 18 , 24 , 34 , 35 ]; and 2 studies used carbon dioxide fluid [ 23 , 26 ]. Three studies used a suspension of the herbal formula Guilingji [ 15 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the rat ischemia/reperfusion model, ginsenoside Rb1 can increase the relative abundance of Lactobacillus and gamma-aminobutyric acid receptors to reduce the proinflammatory cytokines for the improvement of neuroprotection ( Chen et al., 2020 ). In the rats induced by D-galactose, ginseng decoction called Dushen Tang showed good curative ability for memory impairment by up-regulating Bacteroidetes and down-regulating Lactobacillus ( Wang et al., 2021 ). In the mice with Parkinson’s disease, the treatment with the extract from KRG can improve neuronal function and alleviate Parkinson’s symptoms by up-regulating the relative abundance of Eubacterium and down-regulating the relative abundances of Verrucomicrobia and Ruminococcus ( Jeon et al., 2020 ).…”
Section: Ginseng Treats Various Diseases By Regulating Gut Microbiotamentioning
confidence: 99%
“…Taken together, as a signaling molecule, lactic acid in astrocytes is important to the drug memory (80). Although little research provides the evidence that GM can directly affect drug memory, a previous study has shown that memory disorders in rats with elevated levels of lactic acid, an important biomarker, could be improved by correcting intestinal microbial disorders 10.3389/fpsyt.2022.1046804 (e.g., Lactobacilllus, Bacteroidales, and Bacteroides) (81,82). Therefore, future research on drug memory and reducing relapse may be carried out through GM therapy to interfere with the production and secretion of lactic acid.…”
Section: Gut Microbiota and Drug Memorymentioning
confidence: 99%